A study of dosimetric parameters of new born tissue and adult tissue of some organs. (2022) - Seenappa, L.; Manjunatha, H.C.; Sridhar, K.N.; Nagaraja, N.; Doddamani, Vijaykumar H.
Abstract: We have calculated the radiological parameters such as computerized tomography (CT) numbers effective atomic number (Zeff) and electron density (Nel) of newborn tissue and adult tissue of lung, kidney, heart and brain. Effective atomic number is computed by calculating the molecular, atomic and electronic cross section in the wide energy range of 1 keV–100 keV using WinXCOM. The new born tissue and adult tissue a very similar, but their atomic number, CT number and electron densities differs. This fact helps in the radiography and radiotherapy.